Coping With Water Limitation: Hormones That Modify Plant Root Xylem Development - Ramachandran, Prashanth; Augstein, Frauke; Nguyen, Van; Carlsbecker, Annelie (Frontiers in Plant Science, 2020)
Periods of drought, that threaten crop production, are expected to become more prominent in large parts of the world, making it necessary to explore all aspects of plant growth and development, to breed, modify and select crops adapted to such conditions. One such aspect is xylem development, influencing the size and number of water-transporting xylem vessels, thereby impacting on hydraulic conductance and drought tolerance. Here, we focus on how plants adjust their root xylem as a response to reduced water availability. While xylem response has been observed in a wide array of species, most of our knowledge on the molecular mechanisms underlying xylem plasticity comes from studies on the model plant Arabidopsis thaliana. When grown under water limiting conditions, Arabidopsis rapidly adjusts its development to produce more xylem strands with altered identity, in an abscisic acid (ABA) dependent manner. Other hormones such as auxin and cytokinin are essential for vascular patterning and differentiation, and their balance can be perturbed by stress, as evidenced by the effects of enhanced jasmonic acid signaling, which results in similar xylem developmental alterations as enhanced ABA signaling. Furthermore, brassinosteroids and other signaling molecules involved in drought tolerance can also impact xylem development. Hence, a multitude of signals can affect root xylem properties and, potentially, influence survival under water limiting conditions. Here, we review the likely entangled signals that govern root vascular development, and discuss the importance of taking root anatomical traits into account when breeding crops for enhanced resilience towards changes in water availability.